Effectiveness of Electroconvulsive Therapy for Depression and Cotard’s Syndrome in a Patient with Frontotemporal Lobe Dementia - Kobayashi, Toshiyuki; Inoue, Koju; Shioda, Katsutoshi; Kato, Satoshi (Case Reports in Psychiatry, 2012)
In the field of psychogeriatrics, the differential diagnosis of depression and dementia, as well as the treatment of depression and comorbid dementia, is an important issue. In this paper, the authors present the case of a 72-year-old woman with Cotard’s syndrome and frontotemporal dementia (FTD) who was admitted to a psychiatric hospital with delusions of negation accompanied by depressive symptoms. Pharmacotherapy over a 2-year hospitalization was unsuccessful, and she was subsequently transferred to our university hospital. A total of 18 sessions of electroconvulsive therapy released her from psychomotor inhibition, appetite loss, and Cotard’s delusions. The indication for electroconvulsive therapy in patients with dementia is discussed.